HISTORICAL CONDITIONS FOR THE EMERGENCE OF THE JADIDISM IN BUKHARA (Scientific journal of the Fergana State University, 2024)
This article is devoted to the political, socio-philosophical foundations of Bukhara jadidism in the enlightened ideas of the representatives of the Jadid movement, which arose in Turkestan in the middle of the XIX century and the beginning of the XX century. The article philosophically analyzes the views of modern thinkers such as Ahmad Donish, Sadriddin Ayni, Abdurauf Fitrat in social life.